2021
DOI: 10.2991/assehr.k.210715.069
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Students’ Critical and Creative Thinking Skills

Abstract: This study aims to profile the critical and creative thinking skills of high school students in science. The research was employed a quantitative descriptive method. The participants involved in the research were consisted of 108 students for critical thinking skill measurement and 129 students for creative thinking skill assessment. The sample was determined by random cluster sampling. The students' critical thinking skills was measured using 5 essay questions which assess aspects of reasoning, inferencing, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…On the other hand, from the analysis of student performance assessment, it can be stated that the 21st-century skills of students are still in the low category with an average score of 49.61. The research results strengthened the result of this analysis by Alfitriyani et al (2021), which states that students' critical thinking and creative thinking skills are still in the low category.…”
Section: Introductionsupporting
confidence: 61%
“…On the other hand, from the analysis of student performance assessment, it can be stated that the 21st-century skills of students are still in the low category with an average score of 49.61. The research results strengthened the result of this analysis by Alfitriyani et al (2021), which states that students' critical thinking and creative thinking skills are still in the low category.…”
Section: Introductionsupporting
confidence: 61%
“…It is linear eith earlier research that found there are not any differences found based on gender (Sari et al 2019) .There are various solutions to develop creative thinking skills. Based on earlier research, creative thinking will improve by being involved in the PBL process, applying the RICOSRE learning model, giving project briefs, PjBL implementation with Instagram media, and using the STEM education learning approach, combining hands-on experimentation with creative model-construction, the storytelling strategy (Alfitriyani, Pursitasari, and Kurniasih 2021;Ersoy and Başer 2014;Habibi et al 2020;Marianti and Rahayuningsih 2022;Mierdel and Bogner 2019;Sirajudin, Suratno, and Pamuti 2021;Tabieh et al 2020)one of the alternatives to the learning activity that could be used as a tool for improving the basic skills needed in this century in Science, Technology, Engineering, and Mathematics (STEM.…”
Section: Resultsmentioning
confidence: 99%
“…The unique expressions or original solutions are usually not commonly found in references or submitted by people (Nurhalizah et al, 2020). Elaboration is indicated the level of detail describing an argument (Huang et al, 2020), link one information with those from different disciplines (Wijayati et al, 2019), developing detailed ideas (Sugiyanto et al, 2018), itemizing ideas or answers given (Nurhalizah et al, 2020), and add meaning to the argument put forward (Alfitriyani, Pursitasari, & Kurniasih, 2021).…”
Section: Introductionmentioning
confidence: 99%